RETRACTED: Apolipoprotein E-Mimetic Peptide COG1410 Promotes Autophagy by Phosphorylating GSK-3β in Early Brain Injury Following Experimental Subarachnoid Hemorrhage - Li, Xinshen; Peng, Jianhua; Pang, Jinwei; Wu, Yue; Huang, Xueping; Li, Yong; Zhou, Jian; Gu, Long; Sun, Xiaochuan; Chen, Ligang; Vitek, Michael P.; Jiang, Yong (Frontiers in Neuroscience, 2018)
COG1410, a mimetic peptide derived from the apolipoprotein E (apoE) receptor binding region, exerts positive effect on neurological deficits in early brain injury (EBI) after experimental subarachnoid hemorrhage (SAH). Currently the neuroprotective effect of COG1410 includes inhibiting BBB disruption, reducing neuronal apoptosis and neuroinflammation. However, the effect and mechanism of COG1410 to subcellular organelles disorder have not been fully investigated. As the main pathway for recycling long-lived proteins and damaged organelles, neuronal autophagy is activated in SAH and exhibits neuroprotective effects by reducing the insults of EBI. Pharmacologically elevated autophagy usually contributes to alleviated brain injury, while few of the agents achieved clinical transformation. In this study, we explored the activation of autophagy during EBI by measuring the Beclin-1 and LC3B-II protein levels. Administration of COG1410 notablely elevated the autophagic markers expression in neurons, simultaneously reversed the neurological deficits. Furthermore, the up-regulated autophagy by COG1410 was further promoted by p-GSK-3β agonist, whereas decreased by p-GSK-3β inhibitor. Taken together, these data suggest that the COG1410 might be a promising therapeutic strategy for EBI via promoting autophagy in SAH.